Loyalty and the Sacramentum in the Roman Republican Army - Holbrook, Alexandra (My University, 2003)
Despite the large corpus of scholarly writing about the Roman army, the military oath, or sacramentum, of the late Republican legions has not been studied at length. Since the fall of the Republican was rooted in the struggle for political and military dominance by individuals, the loyalty of the legions to these commanders is of utmost importance. The first chapter focuses on the geographic and social origins of the soldiers of the late Republic, which have been studied extensively and provide a background from which to assess the composition of the army. As well, the conditions of service for this period are significant factors affecting the obedience of soldiers to their commanders, and the second chapter of this thesis places particular emphasis on problems of length of service, pay, booty and plunder, and military discipline. This framework of conditions and characteristics supports the analysis of the sacramentum itself in the third chapter. The textual evidence for the oath, both direct and indirect, are gathered for comparative purposes and applied to historical anecdotes of loyal and disloyal behaviour for the period in question. Conclusions about the religion and psychological impact of the sacramentum complete this assessment of the effectiveness of the Roman military oath in the late Republic.
Keywords: Classics; Classics; Classics